Unveiling how consumers from different cultures engage with Facebook pages - Guftométros, M.; Guerreiro, J.; Loureiro, S. M. C. (2019 ANZMAC Conference Proceedings, 2019)
The aim of the current study is to go further in understanding how Hofstede’s cultural dimensions can contribute to mirror differences between cultures in social media context. The data are extracted from 6750 posts from 225 different Facebook brand pages and 15 different countries. Thus, engagement metrics (e.g., the amount of likes, shares and comments, as well as funny likes) are analyzed through correlation analysis. Findings reveal that countries low in individualism and/or high in power distance share posts more than comment on them. Also, higher scores on individualism tend to be associated with the use of the funny emoticon responses. Finally, Hofstede’s dimensions can still have powerful predictors in social media. The results of this study shed further light on the debate whether or not cultural differences are becoming more/less significant in the increased inter-connectiveness and globalization in the world.